Case Studies of Low-Energy Homes and Sites in Northeastern Kansas and Kansas City Metropolitan Area - Clement, Lorn; Lewis, Katrina; Kingery-Page, Katie (Kansas State Unviersity. College of Architecture, Planning & Design, 2013)
Low-energy housing is defined as housing that conserves both source (energy used off-site) and site energy through a variety of strategies, including a reduction in the use of purchased energy and conscious use of materials and techniques that reduce the embodied energy cost of the home and site.While low-energy housing has been extensively studied by the US Green Building Council and others, research tends to focus upon technologies used in the construction of homes, rather than the full optimization of site and building relationships. In order to explore optimal site-structure relationships for low-energy housing and introduce early design students to fundamental case study practices, three faculty members led a total of forty-four students in a study of three sites. The resulting case study sites include homes ranging in building cost from $150,00-$600,000 and employing a variety of both passive and active energy saving techniques. The case studies can be characterized as: a high-design urban lot home, a rural "earthship" home, and a suburban LEED platinum-certified retirement home. This interdisciplinary research effort included forty-one undergraduate students and three graduate students, all of whom were just beginning the interior architecture and product design program or the landscape architecture program at Kansas State University. The case study pedagogy employed experiential learning during site visits and in the context of teamwork between the two disciples. Students and professors visited the three low‐energy homes on a one day field trip in Kansas and Missouri. The case studies’goal was to shed light on the interplay between interior (building) concerns and exterior (site) concerns in the creation of low‐energy environments that are functional and beautiful. The authors wish to thank Kansas State University for supporting this effort through a university small research grant.
Keywords: Low-energy housing; Sustainable design; Site-structure relationships